2022
DOI: 10.7150/thno.65427
|View full text |Cite
|
Sign up to set email alerts
|

Garlic exosome-like nanoparticles reverse high-fat diet induced obesity via the gut/brain axis

Abstract: Background: Obesity is becoming a global epidemic and reversing the pathological processes underlying obesity and metabolic co-morbidities is challenging. Obesity induced chronic inflammation including brain inflammation is a hallmark of obesity via the gut-brain axis. The objective of this study was to develop garlic exosome-like nanoparticles (GaELNs) that inhibit systemic as well as brain inflammatory activity and reverse a HFD induced obesity in mice. Methods: GELNs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 109 publications
(125 reference statements)
1
69
0
Order By: Relevance
“…Oat bran meal was dissolved in PBS and then incubated in a 37 °C water bath for 30 min for supernatant collection and subsequent centrifugation [ 29 ]. Root vegetables, such as carrot [ 30 ], garlic [ 31 , 32 , 33 ], ginger [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], ginseng [ 42 , 43 ], and turmeric [ 44 ], and leafy vegetables including cabbage [ 45 ], were prepared similarly to fruits by blending them with or without additional PBS pre- or post-grinding.…”
Section: Isolation and Characterization Methods Of Pdnvsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oat bran meal was dissolved in PBS and then incubated in a 37 °C water bath for 30 min for supernatant collection and subsequent centrifugation [ 29 ]. Root vegetables, such as carrot [ 30 ], garlic [ 31 , 32 , 33 ], ginger [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], ginseng [ 42 , 43 ], and turmeric [ 44 ], and leafy vegetables including cabbage [ 45 ], were prepared similarly to fruits by blending them with or without additional PBS pre- or post-grinding.…”
Section: Isolation and Characterization Methods Of Pdnvsmentioning
confidence: 99%
“…Xu et al showed that oral administration of DiR labeled oat-derived nanovesicles resulted in signal detection in the brain at 1 h post gavage with a gradual decrease after 6 h and preferential uptake by microglial cells in the brain [ 29 ]. Similarly, Sundaram et al showed that garlic-derived nanovesicles given orally traveled to the brain approximately at the same amount as the liver and intestine [ 33 ]. Specifically, brain microglial cells but not neuronal cells selectively took the garlic-derived nanovesicles [ 33 ].…”
Section: Characteristics Of Unmodified Pdnvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among which PA has shown interaction with mammalian target of rapamycin (mTOR) which results in cell growth and proliferation 31 and since it is mitosis phospholipid, and highly fusogenic with calcium presence which induces inter-vesicular fusion 32 . Contains high PA composition, garlic ELNs also mostly taken by microglial cells by forming garlic ELN/BASP1 complex, helps in mitigating brain inflammation 33 . Based on these studies further question has been raised whether these phospholipids along with their presence and composition are having any role in getting into their target cells.…”
Section: Uptake Biodistribution and Bioavailabilitymentioning
confidence: 99%
“…Garlic ELNs taken up the microglial cells and inhibits brain inflammation. They help in the downregulation of cMyc gene mediated expression of STING activity which leads to reduce the activities of pro-inflammatory cytokines including IFN-γ and TNF-α 33 . Whereas IFN-γ- IDO1 interaction that usually activates the AHR pathway contributes to the attenuation of development of obesity.…”
Section: Cargoes Of Edible Exosome-like Nanoparticlesmentioning
confidence: 99%